Spatial control of AMPK signaling at subcellular compartments - Chauhan, Anoop Singh (Crit Rev Biochem Mol Biol, 2020)
AMP-activated protein kinase (AMPK) is a master regulator of energy homeostasis that functions to restore the energy balance by phosphorylating its substrates during altered metabolic conditions. AMPK activity is tightly controlled by diverse regulators including its upstream kinases LKB1 and CaMKK2. Recent studies have also identified the localization of AMPK at different intracellular compartments as another key mechanism for regulating AMPK signaling in response to specific stimuli. This review discusses the AMPK signaling associated with different subcellular compartments, including lysosomes, endoplasmic reticulum, mitochondria, Golgi apparatus, nucleus, and cell junctions. Because altered AMPK signaling is associated with various pathologic conditions including cancer, targeting AMPK signaling in different subcellular compartments may present attractive therapeutic approaches for treatment of disease.